Hormonal Contraceptive Use Related to Menopausal Age - Destri Safhira Siahaan; Adek Amansyah; Irza Haicha Pratama (Archives of The Medicine and Case Reports, 2021)
The change in the pattern and timing of menopause is an exciting and exploratory phenomenon that requires more detailed research to be carried out using hormonal contraception. This study was aimed to explore the relationship between hormonal contraceptive use and menopausal age. This study used a cross-sectional design. The study was conducted at Royal Prima General Hospital Medan from May to August 2021. A total of 68 research subjects participated in this study with the following inclusion criteria: menopausal women, aged 50-60 years, using hormonal contraceptives (pills, injections, implants), able to remember history previous contraceptive use. This study uses primary data obtained directly from guided interviews with respondents. Participants were dominated by ≥ 55 years old women with 57 people (83.81%), 62 Muslims (91.2%), menarche age >13 years as many as 28 people (41.2%). The number of children 2-4 were 32 people (47.1%) with an average menopause age of 51.93 and the smallest for 1 was 8 people (11.8%) with an average menopause age of 50.37. There were 49 users of hormonal contraception (72.1%) and 48 people (70.6%). In conclusion, we found that the use of hormonal contraceptives is significantly related to menopausal age.